Predictors of surgical site infection following reconstructive flap surgery: A multi-institutional analysis of 37,177 patients - Hassan, Bashar; Abou Koura, Abdulghani; Makarem, Adham; Abi Mosleh, Kamal; Dimassi, Hani; Tamim, Hani; Ibrahim, Amir (Frontiers in Surgery, 2023)
Purpose: The rate of surgical site infection (SSI) following reconstructive flap surgeries (RFS) varies according to flap recipient site. It has been reported to be 4.9% in breast reconstructive procedures and up to 16.5% in head and neck reconstructive procedures. SSI is a common and unfortunate complication of RFS leading to mortality and morbidity. Here, we conduct the first and largest study to compare the incidence and determine the predictors of SSI following RFS across reconstruction sites. Materials and Methods: The National Surgical Quality Improvement Program database was queried for patients undergoing any flap procedure from years 2005 to 2020. RFS involving grafts, skin flaps, or flaps with unknown reconstruction site were excluded. Patients were stratified according to reconstruction site: breast, trunk, head and neck (H&N), upper extremities (UE) and lower extremities (LE). The primary outcome was the incidence of SSI within 30 days following surgery. Descriptive statistics were calculated. Bivariate analysis and multivariate logistic regression were performed to determine predictors of SSI following RFS. Results: 37177 patients underwent RFS, of whom 7.5% (n=2776) developed SSI. A significantly greater proportion of patients who underwent LE (n=318, 10.7%) and trunk (n=1091, 10.4%) reconstruction developed SSI compared to those who underwent breast (n=1201,6.3%), UE (n=32, 4.4%), and H&N (n=100, 4.2%) reconstruction (p<.001). Longer operating times were significant predictors of SSI following RFS across all sites. The strongest predictors of SSI were presence of open wound following trunk and H&N reconstruction [adjusted odds ratio (aOR) 95% confidence interval (CI) 1.82 (1.57-2.11) and 1.75 (1.57-1.95)], disseminated cancer following LE reconstruction [aOR (CI) 3.58 (2.32-5.53)], and history of cardiovascular accident or stroke following breast reconstruction [aOR (CI) 16.97 (2.72-105.82)]. Conclusion: Longer operating time was a significant predictor of SSI regardless of reconstruction site. Reducing operating times through proper surgical planning might help mitigate the risk of SSI following RFS. Our findings should be used to guide patient selection, counseling, and surgical planning prior to RFS.